2001
DOI: 10.1080/07448480109596299
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake, Body Mass Index, Exercise, and Alcohol: Are College Women Following the Dietary Guidelines for Americans?

Abstract: Study findings suggest that college women practice diet and health behaviors that contradict the 1995 Dietary Guidelines for Americans. To confirm this hypothesis, the authors surveyed the diet, exercise, and health habits of 60 female students enrolled in three university aerobics courses. They measured height and weight to calculate body mass index (BMI) and assessed physical activity, using the Self-Reported Physical Activity scale. To estimate food and nutrient intake, they used 3-day food records. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 31 publications
6
79
0
6
Order By: Relevance
“…19 The prevalence rate of obesity in the current study is similar to the studies done by Majeed and Anding et al and it is slightly higher than the study done in Abha by Hakeem et al among the female college students. [26][27][28] Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation. Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation.…”
Section: Discussionmentioning
confidence: 99%
“…19 The prevalence rate of obesity in the current study is similar to the studies done by Majeed and Anding et al and it is slightly higher than the study done in Abha by Hakeem et al among the female college students. [26][27][28] Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation. Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Algumas pesquisas avaliaram os hábitos alimentares de estudantes universitários [4][5][6][7][8] , sendo observada, em sua maioria, baixa prevalência de alimentação saudável, com elevada ingestão de alimentos doces e gordurosos e baixa ingestão de frutas e hortaliças. Segundo Vieira et al 8 , os maus hábitos alimentares desses universitários poderiam estar sendo influenciados pelos novos comportamentos e relações sociais, sugerindo indícios de compulsão alimentar em alguns alunos que, ansiosos, podem transformar a alimentação em "válvula de escape" para as situações de estresse físico e mental.…”
Section: N T R O D U ç ã Ounclassified
“…No entanto, estudos que relatam o comportamento alimentar e de atividade física de universitários são limitados 3,5,7 . Assim, não se tem estabelecido se as faculdades e universidades proporcionariam oportunidades para uma influên-cia positiva de comportamentos com relação à prática de atividade física, nutrição e manutenção de peso de adolescentes e de adultos jovens em um ambiente educacional 3 .…”
Section: N T R O D U ç ã Ounclassified
“…The CHOICES program Decreased physical activity and poor nutrition [15][16][17], as well as other factors such as inadequate sleep [18] and stress [19] are leading contributors to a variety of shortand long-term negative health consequences among young adults. The CHOICES (Choosing Healthy Options in College Environments) trial was designed to develop and test innovative strategies to prevent unhealthy weight gain in students attending 2-year colleges [20].…”
mentioning
confidence: 99%